Effectiveness of copper-containing fungicide liquid based on domestic copper sulfate against apple scab (Experimental biology, 2015)
Studied the effect of the fungicidal copper-bearing fluid as an effective way of increasing the productivity and sustainability of apple to scab. The test showed a stable effect of the copper-bearing fluid to increase the biological effectiveness (97%) against given diseases.
Keywords: copper-bearing liquid fungicide; scab; efficiency; stability; productivity